PANCASILA SEBAGAI ETIKA POLITIK DAN HUKUM NEGARA INDONESIA [Pancasila as Political Ethics and Indonesian State Law] - Thomas Tokan Pureklolon (Law Review, 2020)
AbstractPancasila is not only a source of derivation of legislation, but also a source of morality, especially in relation to the legitimacy of power, law and various policies in the implementation and administration of the state. The existence of the first precept of "The Almighty Godhead", and the second precept of "Fair and Civilized Humanity" is the source of moral values for national and state life. The state of Indonesia which is based on the first precept of "The Almighty God" is not a "theocracy" state which bases state power and state administration on religious legitimacy. The power of the head of state is not absolute based on religious legitimacy but based on legal legitimacy and democratic legitimacy. Therefore, the principle of the principle of "Godhead of the Almighty" has more to do with moral legitimacy. This is what distinguishes the Almighty God from theocracy. The writing method in this journal is a qualitative method, with an interdisciplinary approach. Although in the Indonesian state it is not based on religious legitimacy, morally the life of the state must be in accordance with the values derived from God, especially the law and morals in the life of the state.Keywords: Political Ethics, Law, Pancasila AbstrakPancasila tidak hanya merupakan sumber derivasi peraturan perundang-undangan, melainkan juga merupakan sumber moralitas, terutama dalam hubungannya dengan legitimasi kekuasaan, hukum serta berbagai kebijakan dalam pelaksanaan dan penyelenggaraan negara. Eksistensi sila pertama “Ketuhanan Yang Maha Esa”, serta sila kedua “Kemanusiaan yang Adil dan Beradab” merupakan sumber atas nilai-nilai moral bagi kehidupan kebangsaan dan kenegaraan. Negara Indonesia yang berdasarkan sila pertama “Ketuhanan Yang Maha Esa” bukanlah negara “teokrasi” yang mendasarkan kekuasaan negara dan penyelenggaraan negara pada legitimasi religius. Kekuasaan kepala negara tidak bersifat mutlak berdasarkan legitimasi religius, melainkan berdasarkan legitimasi hukum serta legitimasi demokrasi. Oleh karena itu asas sila “Ketuhanan Yang Maha Esa” lebih berkaitan dengan legitimasi moral. Hal inilah yang membedakan negara yang Berketuhanan Yang Maha Esa dengan negara teokrasi. Metode penulisan dalam jurnal ini adalah metode kualitatif, dengan pendekatan interdisipliner. Walaupun dalam negara Indonesia tidak mendasarkan pada legitimasi religius, secara moralitas kehidupan negara harus sesuai dengan nilai-nilai yang berasal dari Tuhan, terutama hukum serta moral dalam kehidupan negara.Kata kunci: Etika Politik, Hukum, Pancasila